Between Phraseology and Rhetoric: The Translatability of Idiomatic Collocations and al-badīʿ devices in Risāla fī Faḍl al-Andalus - Mahjoubi, Jihad (Anaquel de Estudios Árabes, 2026)
This study examines figurative collocations in Ibn Ḥazm’s Risāla fī faḍl al-Andalus (Epistle in Praise of al-Andalus, 994–1064) from a threefold perspective: phraseological, rhetorical, and translatological. The analysis focuses on a representative selection of passages where highly fixed multiword units with strong aesthetic value are concentrated. Their main morphosyntactic configurations are described, highlighting recurrent structural and semantic patterns characteristic of classical Arabic prose, and connected to rhetorical devices of ʿilm al-badīʿ such as metaphor, hyperbole, parallelism, and rhymed prose. Translation strategies into Spanish are also examined—including fixed equivalents, cultural modulations, paraphrases, and functional adaptations—while reflecting on the constant tension between formal fidelity and idiomatic fluency. Findings reveal that translating these expressions is particularly challenging due to the archaic nature of the text, its rhetorical density, and cultural load, thus raising the fundamental question of whether to preserve the collocational character or to prioritize meaning and naturalness in the target language.
Keywords: Ibn Ḥazm; figurative collocations; Risāla fī Faḍl al-Andalus; Arabic phraseology; ʿilm al-badīʿ; Arabic-Spanish translation